What Do the Finfluencers Advise? - Krugell, Waldo; Jansen van Rensburg, Johnny (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This study examines the rapidly evolving landscape of investment access and advice, focusing on the role of social media “finfluencers” in shaping investment decisions. The research explores what advice South African investors can get, particularly in asset allocation and portfolio strategies. Prior Work: Building on the work of Choi (2022) and others, this paper compares personal financial advice given in the more famous self-help texts with what is available on platforms like TikTok. Approach: A qualitative analysis was conducted, examining the content of popular TikTok videos related to personal finance. The study focused on key investment themes such as equity portfolio allocation, lifecycle portfolio strategies, international diversification, and active vs. passive fund management. Results: The findings reveal an abundance of personal finance advice but a notable lack of comprehensive investment guidance. The investment advice is predominantly focused on tax-free savings accounts, exchange-traded funds, and the promotion of long-term wealth accumulation (often via dividend investing). Implications: This study provides valuable insights for academics and financial regulators into the scope and limitations of investment advice disseminated via social media, particularly for South African investors. Behavioral finance biases (e.g., framing and herd effects) appear to play a role in how such advice is presented and consumed. Value: The paper contributes to the growing body of literature on digital finance by offering a focused analysis of the role of “finfluencers” in shaping investment behavior in an emerging market context.